Effects of dietary mannan oligosaccharide on the survival, growth, immunity and digestive enzyme activity of freshwater crayfish, Cherax destructor Clark (1936) - Sang, H.; Fotedar, Ravi; Filer, K. (Blackwell Scientific Publications, 2011)
The aim of this experiment was to determine the effects of dietary supplementation of Bio-Mos® as a source of mannan oligosaccharide (MOS) on the growth, survival, immunity and digestive enzyme activity of freshwater crayfish, Cherax destructor (yabby). A basal diet and another diet with 0.4% of Bio-Mos® supplemented to the basal diet were formulated. Each diet was provided to eight yabbies (35.14 ± 0.48 g, initial weight) replicated 3 times in individual 250-L plastic cylindrical tanks for a duration of 56 days. Each tank was provided with an independent recirculating water system filtered with a biological filtration. Growth parameters such as weight, specific growth rate and average weekly gain of Bio-Mos®-fed yabbies were higher (P < 0.05) than yabbies fed the control diet. Total haemocyte count, granular cells and semi-granular cells were also higher in the yabbies fed Bio-Mos® diet. Protease activity was higher in hepatopancreas, and amylase activity was higher in the guts of yabbies fed Bio-Mos® diet. The results implies that supplementation of MOS through Bio-Mos® can effectively improve growth and immunological condition of yabbies.